EVALUATION OF THYROID DISORDERS IN SUDANESE PATIENTS WITH DOWN SYNDROME - FatahAlrahman, Ayman; Babiker, A.; Khalid, Mosab .O.; Allzain, Haghamad Allzain (International Journal of Research -GRANTHAALAYAH, 2020)
Down syndrome is the most common life compatible chromosomal disorder responsible for the majority of mental retardation and deaths in infancy and childhood. The current study intended to evaluate the thyroid disorders in Sudanese patients with Down syndrome by assessment of thyroid function tests (T3, T4 & TSH) . It was descriptive case control study, carried out in Khartoum, the capital of Sudan, from March to July 2018. It included fifty (50) participants, thirty (30) of them as case group with Down syndrome and twenty (20) normal healthy subjects as control group. Their ages ranged from seven (7) to twenty eight (28) years. The study findings showed significant variation in TSH level with mean (2.66 ), (1.67 ) in case and control group respectively with P. value (0.001). There was also significant variation when compared children and adults mean TSH level (1.88 ),(2.59 ) with P. value of (0.03). There was insignificant differences in T3 level with mean SD(1.04 .32),(1.11 ) between case and control group respectively with P. value of (0.08) . There was also insignificant difference in T4 level with mean (6.09 ),(6.40 ) in case and control group respectively with P. value of (0.7). There were also insignificant differences in T4 and T3 levels between the age groups. As regard to the gender of the patients, there were insignificant differences of TSH, T4, and T3